2021
DOI: 10.1101/2021.04.08.21255055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct and indirect effectiveness of mRNA vaccination against SARS-CoV-2 infection in long-term care facilities in Spain

Abstract: Objectives: To estimate indirect and total (direct plus indirect) effects of COVID-19 vaccination in residents in long-term care facilities (LTCF). Design: Registries-based cohort study including all residents in LTCF 65 years or older offered vaccination between 27 December 2020 and 10 March 2021. Risk of SARS-CoV-2 infection following vaccination was compared with the risk in the same individuals in a period before vaccination. Risk in non-vaccinated was also compared to a period before the vaccination progr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
1
12
1
2
Order By: Relevance
“…Our VE against infection was lower than in previous studies from similar settings [4], [6], [7]. Since this cohort was PCR-tested every 5-6 days throughout the outbreak, we believe that the risk for missing asymptomatic cases was minimal while in other studies under-ascertainment of asymptomatic infection may have occurred.…”
Section: Discussioncontrasting
confidence: 52%
“…Our VE against infection was lower than in previous studies from similar settings [4], [6], [7]. Since this cohort was PCR-tested every 5-6 days throughout the outbreak, we believe that the risk for missing asymptomatic cases was minimal while in other studies under-ascertainment of asymptomatic infection may have occurred.…”
Section: Discussioncontrasting
confidence: 52%
“…Two large Spanish studies in longterm care facility residents reported similar single-dose BNT162b2 vaccine effective ness estimates to those reported here; however, these studies have limitations of shorter dosing intervals than used in the UK setting and little or no routine asymptomatic screening. 15,16 We observed reduced hazards of infection in the immediate post-vaccination period (0-13 days) for ChAdOx1, which cannot be attributed to protective effects of the vaccine but might be because recently vaccinated long-term care facilities were less likely to have ongoing outbreaks of infection. Guidance on risk assessmentbased deferral of vaccination in long-term care facilities with active outbreaks was introduced at the end of December, 2020, 35 and is likely to have disproportionately affected facilities predominantly using ChAdOx1, which was deployed later than BNT162b2.…”
Section: Chadox1 Bnt162b2mentioning
confidence: 68%
“…6 Consequently, trial estimates of vaccine efficacy might not be generalisable to long-term care facility residents because of age-related differences in vaccine-induced immune responses. [7][8][9] Observational data from post-licensure studies in older adults are emerging, [10][11][12] and although a small number of preprint articles have reported on populations in long-term care facilities, [13][14][15][16] the study populations were exclusively vaccinated with BNT162b2 at the manufacturer-recommended dosing interval, and regular asymptomatic screening was rarely done.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 30 studies, 26 investigated the efficacy/effectiveness of COVID-19 vaccines in preventing SARS-CoV-2 infections, based on reports of number of symptomatic and asymptomatic PCR-positive individuals [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][22][23][24][25][26][27][28][29][30][31] (Table 1). Studies were conducted in eight different countries (Denmark (n=1), Israel (n=4), Italy (n=1), Qatar (n=1), Spain (n=2), Sweden (n=1), UK (n=8), US (n=7)) and one study was multi-centric [22].…”
Section: Prevention Of Infectionmentioning
confidence: 99%